1988
DOI: 10.1159/000238602
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Increase in Human Peripheral Blood and Bone Marrow Mononuclear Cells following Administration of Methylglyoxal bis(guanylhydrazone)

Abstract: Eight patients who had refractory leukemia and 1 patient with refractory multiple myeloma were treated with the polyamine biosynthesis inhibitors methylgloxal bis(guanylhydrazone) (MGBG) and difluoromethylornithine (DFMO). After the first dose of MGBG there was an increase in polyamine content in the mononuclear cells of both the peripheral blood and the bone marrow despite the administration of DFMO in all patients with leukemia. Putrescine levels increased in the mononuclear cells of all patients, cellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been suggested that the polyamine transporter may provide a useful means of directing cytotoxic agents to tumour cells in vivo [8]. Recently, Maddox and associates [22] showed an increase in the cellular content of MGBG following DFMO therapy in patients with haematological malignancies. MGBG is known to be transported by the polyamine uptake system [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the polyamine transporter may provide a useful means of directing cytotoxic agents to tumour cells in vivo [8]. Recently, Maddox and associates [22] showed an increase in the cellular content of MGBG following DFMO therapy in patients with haematological malignancies. MGBG is known to be transported by the polyamine uptake system [6].…”
Section: Discussionmentioning
confidence: 99%